2014
DOI: 10.1186/1472-6831-14-139
|View full text |Cite
|
Sign up to set email alerts
|

Association between moderate to severe psoriasis and periodontitis in a Scandinavian population

Abstract: BackgroundThe aim of the present study was to compare the prevalence of periodontitis and alveolar bone loss among individuals with psoriasis and a group of randomly selected controls.MethodsFifty individuals with psoriasis and 121 controls completed a structured questionnaire, and were examined clinically and radiographically. Oral examination included numbers of missing teeth, probing pocket depth (PPD), clinical attachment level (CAL), presence of dental plaque and bleeding on probing, as well as alveolar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(104 citation statements)
references
References 35 publications
8
89
2
5
Order By: Relevance
“…Later, observational studies have confirmed these findings . However, they have shown some controversial results and limitations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Later, observational studies have confirmed these findings . However, they have shown some controversial results and limitations.…”
Section: Discussionmentioning
confidence: 89%
“…However, they have shown some controversial results and limitations. Among them, the use of retrospective data obtained from medical records, indexes for characterizing periodontitis, small samples, self‐reported information about periodontal, and psoriasis conditions …”
Section: Discussionmentioning
confidence: 99%
“…One study was excluded because it compared the risk of periodontitis among subjects with and without psoriasis (and did not compare the risk of psoriasis in subjects with and without periodontitis) . Therefore, five studies (two cohort studies and three case–control studies) met the predefined eligibility criteria and were included in the meta‐analysis . The bibliographies of these five studies were manually reviewed for additional relevant studies, but no further studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…der chronisch spontanen Urtikaria (csU) und Psoriasis, wird/wurde traditionell eine Fokussuche durchgeführt, die vorrangig Ausschluss, gegebenenfalls Behandlung eines entzündlichen Geschehens im Hals-Nasen-Ohren-Bereich und im Zahn-Mund-Kiefer-Bereich beinhaltet. Während lange Zeit diese Maßnahmen bona fide ohne robuste wissenschaftliche Grundlage durchgeführt wurden, belegen nun zahlreiche kürzlich erschienene Arbeiten [1,2,3,4,5] eine erhöhte Inzidenz von Parodontitis bei Patienten mit Psoriasis gegenüber der Normalbevölkerung und legen eine ähnliche Entzündungskaskade bei beiden Krankheitsbildern nahe.…”
Section: Transfer In Die Praxis Von Prof Dr Vera Mahler (Langen)unclassified